Cobalt–boron/nickel–boron nanocomposite with improved catalytic performance for the hydrolysis of ammonia borane. (19th October 2015) - Zou, Yongjin; Cheng, Jun; Wang, Qingyong; Xiang, Cuili; Chu, Hailiang; Qiu, Shujun; Zhang, Huanzhi; Xu, Fen; Liu, Shusheng; Tang, Chengying; Sun, Lixian
Abstract: A cobalt–boron/nickel–boron (Co–B/Ni–B) nanocomposite was synthesized in a two-step process by in situ reduction of nickel and cobalt salts. Characterization of the nanocomposite using X-ray diffraction, scanning electron microscopy, and Brunauer–Emmett–Teller adsorption analysis showed that the Co–B nanoparticles were well dispersed on the Ni–B surface. Enlisted as a catalyst in the hydrolysis of ammonia borane (AB) for hydrogen generation (HG), the nanocomposite exhibited better catalytic activity than Co–B and Ni–B at room temperature; the HG rate was 1368.2 mL min −1 g −1 at 25 °C in a 1.5 wt.% AB solution, with a low activation energy of 33.5 kJ mol −1 . The effect of the complexing agent (sodium citrate) on the nanocomposite's catalytic activity was also investigated. In addition, recycling tests showed that Co–B/Ni–B was still highly active and preserved 84% of its initial catalytic activity after 11 recover-and-reuse cycles. Highlights: Co–B/Ni–B amorphous composite catalyst was prepared by two-step chemical reduction. Synergetic interaction between Ni–B and Co–B enhanced catalytic activity of Co–B/Ni–B. Co–B/Ni–B nanocomposite showed high stability for the hydrolysis of AB. Activation energy of 33.5 kJ mol −1 is lower than most reported values.